Frequency of latent equine herpesvirus type-1 infection among a sample of horses in the central North Island of New Zealand. Issue 1 (2nd January 2020) - Bueno, IMC; Pearce, P; Dunowska, M
ABSTRACT: Aim: To estimate the frequency of infection with equine herpesvirus type-1 (EHV-1) among horses from the central North Island of New Zealand, including the frequency of detection of the D752 genotype. Methods: Samples of retropharyngeal lymph nodes (RLN) and submandibular lymph nodes (SLN) were dissected from the heads of 63 horses that were humanely killed for various unrelated reasons between March and November 2015. DNA extracted from these tissues was subjected to enrichment for EHV-1 sequences by hybridisation with biotin-labelled EHV-1 specific probe, followed by recovery of EHV-1 sequences on streptavidin-coated magnetic beads. Enriched samples were tested for the presence of EHV-1 using nested quantitative real-time PCR. The EHV-1 amplicons were sequenced to determine the genotype of the virus. Results: The median age of the horses was 6 (min 2, max 30) years, and 47/63 (75%) were Thoroughbreds. EHV-1 DNA was detected in RLN samples from 6/63 (10%) horses, and three of these horses were also positive for EHV-1 DNA in SLN. The remaining horses were negative for EHV-1 DNA in both RLN and SLN samples. The N752 genotype was detected in all positive samples and the D752 genotype was not detected in any of the samples. Conclusions: EHV-1 continues to circulate among horses in New Zealand. The frequency of latent EHV-1 infection among sampled horses may have been underestimated due to the sensitivity limit of the assay or because of the limited anatomical sites sampled in the study. Lack of detection of the D752 genotype suggests that infection with this genotype is not common in horses in New Zealand. Clinical Relevance: If live animals are tested for EHV-1 using SLN biopsy it should be kept in mind that negative results do not rule out the presence of latent EHV-1 infection at other sites inaccessible for testing. The RLN appear to be the preferred sample for detection of EHV-1 DNA in horses following recent euthanasia.